Proteostasis in aging-associated ocular disease. (December 2022) - Weinberg, Jasper; Gaur, Mohita; Swaroop, Anand; Taylor, Allen
Abstract: Vision impairment has devastating consequences for the quality of human life. The cells and tissues associated with the visual process must function throughout one's life span and maintain homeostasis despite exposure to a variety of insults. Maintenance of the proteome is termed proteostasis, and is vital for normal cellular functions, especially at an advanced age. Here we describe basic aspects of proteostasis, from protein synthesis and folding to degradation, and discuss the current status of the field with a particular focus on major age-related eye diseases: age-related macular degeneration, cataract, and glaucoma. Our intent is to allow vision scientists to determine where and how to harness the proteostatic machinery for extending functional homeostasis in the aging retina, lens, and trabecular meshwork. Several common themes have emerged despite these tissues having vastly different metabolisms. Continued exposure to insults, including chronic stress with advancing age, increases proteostatic burden and reduces the fidelity of the degradation machineries including the ubiquitin-proteasome and the autophagy-lysosome systems that recognize and remove damaged proteins. This "double jeopardy" results in an exponential accumulation of cytotoxic proteins with advancing age. We conclude with a discussion of the challenges in maintaining an appropriate balance of protein synthesis and degradation pathways, and suggest that harnessing proteostatic capacities should provide new opportunities to design interventions for attenuating age-related eye diseases before they limit sight.